(untitled) (Research, Society and Development, 2020)
The youths from Ceará are poorly articulated politically, and there is, for example, no youth council in most municipalities in Ceará. It becomes relevant to develop dialogical relationships with young people, especially residents of rural and peripheral locations, so that they can intervene in favor of local and state policies in matters that concern them. The objective was to qualify technically and politically young people economically less favored about the Brazilian socio-political reality, them to social engagement and to act as defenders of a popular project of society with a view to greater social justice. The study was supported by action-based research mediated by Pedagogy of Alternation, which provided training for 45 young people from eight cities: Fortaleza, Limoeiro do Norte, Itapipoca, Tianguá, Sobral, Crateús, Iguatu and Crato. It was found that young people have little political participation in their municipalities, as they had little knowledge about the elaboration and implementation of public policies, and that these were thought without listening to youth concerns, considering them a social problem. Faced with political empowerment, young people understood their local specificities and established greater engagement in social development and monitoring of youth policies that were intrinsic to them.